2020
DOI: 10.1037/tra0000959
|View full text |Cite
|
Sign up to set email alerts
|

Meditating in virtual reality: Proof-of-concept intervention for posttraumatic stress.

Abstract: We investigate the potential therapeutic application of virtual reality (VR) technology as an aid to meditation practice among persons varying in posttraumatic stress disorder (PTSD) symptoms. Method: In this within-group mixed-methods study, 96 young adults practiced both VR-and non-VRguided meditations and reported on their experience of positive affect (PA), negative affect (NA), other meditative experiences and perceived satisfaction-credibility of each meditation. Results: Participants reported more PA an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 34 publications
(62 reference statements)
7
18
0
Order By: Relevance
“…We note at the outset that responses to post-meditation surveys were always scored at the item level rather than as various sub-scale or total-scale summary scores as is more conventional in the literature. This approach, following previous methods (e.g., Mistry et al, 2020), is preferred to allow a more nuanced investigation of self-reported meditative experiences.…”
Section: Post-meditation Surveysmentioning
confidence: 99%
See 4 more Smart Citations
“…We note at the outset that responses to post-meditation surveys were always scored at the item level rather than as various sub-scale or total-scale summary scores as is more conventional in the literature. This approach, following previous methods (e.g., Mistry et al, 2020), is preferred to allow a more nuanced investigation of self-reported meditative experiences.…”
Section: Post-meditation Surveysmentioning
confidence: 99%
“…Finally, the study involved six groups of dependent variables assessed by numeric ratings, specifically, positive affect (mDES-PA), negative affect (mDES-NA), Buddhist affective states (BASS), normative meditative experiences (MEQ), meditation breath attention scores (MBAS), and a general satisfaction survey first used by that was in turn modeled after the questionnaire developed by Devilly and Borkovec (2000). Taken together, this is the very same experimental model and set of dependent measures as was undertaken by Mistry et al (2020), with the addition of MBAS, and thus constituted a comparison study whereby the previous publication utilized the display of computer simulated environments, whereas the current study depicted 360°videos of pre-recorded instructor-guided meditations. Also following the methods undertaken in the previous study (Mistry et al, 2020), we surveyed responses to the VR and non-VR meditations at the item level using multivariate ANOVA to control for multiple comparisons with two-tailed statistical significance determined at p < .05 for analyses of variance and post-hoc tests of means (2-tailed).…”
Section: Data Analysesmentioning
confidence: 99%
See 3 more Smart Citations